The role of ICT in education with special reference to classroom teachings - A literature review - Dr. Manzoor Ahmad Wagay (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
In the field of education( ICT) has done a tremendous progress by modifying the system of education to some extant. Over the past few decades, information and communications technology (ICT) has become more important to educational institutions. There are wide of knowledge, and findings exists to enquire and study the use of ICT in the process of learning and teaching in educational institutions. Today in many developed and developing countries, most investments are made in this area and ICT is regarded as a key instrument within the field of education. This research inspects the application of ICT in the classrooms. This study will explore the role of information and communication technology in enhancement of teaching and learning process, academic achievement of students and attempt to show the student and teachers attitude towords the learning with technolog. Proper usage and utilization of modern tools and techniques by which teaching learning process is made interactive and indefinite will be precisely discussed.